The making of the modern child : children's literature and childhood in the late eighteenth century - O'Malley, Andrew, 1968- (Children's literature and culture, 2003)
Explores how the concept of childhood in the Victorian era was constructed through the ideological work performed by children's literature, as well as contemporary pedagogical and medical writing.